PENDIDIKAN DAN PELATIHAN PENGELASAN SMAW BAGI ANGGOTA KARANG TARUNA RT 06 RW 01 SUMBERSARI LOWOKWARU MALANG - Etik Puspitasari; Suyanta Suyanta; Bambang Sulistiyono; Imam Mashudi; Arif Rochman Fachrudin (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2016)
Youth who have positions with strategic location surrounded by a variety of campus is not always all its members feel mengenyam lecture bench. Some of them are good carpenters and construction workers and construction laborers until now have not had a steady job, sometimes idle. For the Polytechnic of Malang as vocational education institutions felt compelled to help provide a solution in the form of life skills that can be an alternative job or source of livelihood should not require significant funding. One such alternative is the electric welding workshop for the manufacture of trellises, fencing and canopy management can be done together.On the activities of Community Services was conducted education and training SMAW welding pipe joints for members Karangtaruna RT 06 RW 01 Sub Sumbersari Lowokwaru District Malang, as an effort to provide knowledge and skills that can be used to find or create new livelihood alternatives. Training provided includes knowledge and skills about safety in the welding industry, the basic theory Las SMAW, practice basic welding make ridges welding and plate work, the process of measuring and cutting the pipe, the process of grinding, process penyikuan pipe, and welding processes SMAW pipe connection ,Results of the evaluation of training Youth RT 06 RW 01 Sub Sumbersari Lowokwaru District Malang shows that the participants have been able to weld pipe joints with the process SMAW, so that they can obtain alternative employment by working in the workshops welding and has been given a set of welding equipment inverter SMAW they can continue to practice and make the business group's own welding workshop.